THE RELATIONSHIP BETWEEN ACADEMIC STRESS AND CYBERLOAFING BEHAVIOR IN GUIDANCE AND COUNSELING STUDENTS OF PGRI UNIVERSITY OF WEST SUMATRA - Muharammi, Nurul; Triyono, Triyono; Putri, Besti Nora Dwi (Jurnal Konseling Pendidikan Islam, 2025)
This research is motivated by the phenomenon of using the internet for non-academic activities (cyberloafing) during lectures, such as opening social media or watching videos, which students often do in response to academic stress. This study aims to 1) describe the level of academic stress of students, 2) describe cyberloafing behavior, and 3) test the relationship between academic stress and cyberloafing. Data were collected through a cyberloafing and academic stress questionnaire that was tested for validity, namely the validity of cyberloafing (r count = 0.861) and the validity of academic stress (r count = 0.726), as well as the reliability test with Cronbach's alpha for cyberloafing (α = 0.990) and academic stress (α = 0.966), and analyzed using percentage and correlation techniques. The results showed that: Academic stress in students was relatively high with a percentage of 39.47%, cyberloafing behavior was quite high with a percentage of 48.68%, and there was a significant relationship between academic stress and cyberloafing behavior, with a strong correlation (r = 0.61). These findings provide important insights for students to understand how academic stress triggers cyberloafing behavior, as well as for lecturers to develop more effective strategies for minimizing the negative impact of cyberloafing in the academic environment.